Total flavonoids extracted from Penthorum chinense Pursh mitigates CCl4-induced hepatic fibrosis in rats via inactivation of TLR4-MyD88-mediated NF-κB pathways and regulation of liver metabolism - Wang, Sujuan; Li, Wenqing; Liu, Wenxiu; Yu, Lei; Peng, Fu; Qin, Junyuan; Pu, Lin; Tang, Yunli; Xie, Xiaofang; Peng, Cheng (Frontiers in Pharmacology, 2023)
Background: Penthorum chinense Pursh (PCP) is widely utilized in China to treat a variety of liver diseases. It has been shown that flavonoids inhibit inflammation and have the potential to attenuate tissue damage and fibrosis. However, the mechanisms underlying how total flavonoids isolated from PCP (TFPCP) exert their anti-fibrotic effects remain unclear. Methods: The chemical composition of TFPCP was determined using UHPLC–Q-Orbitrap HRMS. Subsequently, rats were randomly assigned to a control group (Control), a carbon tetrachloride (CCl4)-induced hepatic fibrosis model group (Model), a positive control group [0.2 mg/(kg∙day)] of Colchicine), and three TFPCP treatment groups [50, 100, and 150 mg/(kg∙day)]. All substances were administered by gavage and treatments lasted for nine weeks. Simultaneously, rats were intraperitoneally injected with 10% to 20% CCl4 for nine weeks to induce liver fibrosis. At the end of the experiment, the liver ultrasound, liver histomorphological, biochemical indicators, and inflammatory cytokine levels were tested respectively. The underlying mechanisms were assessed using western blot, immunohistochemistry, immunofluorescence, RT-qPCR, and metabolomics. Results: Fourteen flavonoids were identified in TFPCP. Compared with control animals, CCl4-treated rats demonstrated obvious liver injury and fibrosis, manifested as increases in gray values, distal diameter of portal vein (DDPV) and a decrease in blood flow velocity (VPV) in the ultrasound analysis; increased biochemical index values (serum levels of ALT, AST, TBIL, and ALP); marked increases in the contents of fibrotic markers (PC III, COL4, LN, HA) and inflammatory factors (serum TNF-α, IL-6, and IL-1β); and significant pathological changes. However, compared with the Model group, the ultrasound parameters were significantly improved and the serum levels of inflammatory cytokines were reduced in the TFPCP group. In contrast, the expression of TGF-β1, TLR4, and MyD88, as well as the p-P65/P65 and p-IκBα/IκBα ratios, were considerably reduced following TFPCP treatment. In addition, we identified 32 metabolites exhibiting differential abundance in the Model group. Interestingly, TFPCP treatment resulted in the restoration of the levels of 20 of these metabolites. Conclusions: Our findings indicated that TFPCP can ameliorate hepatic fibrosis by improving liver function and morphology via the inactivation of the TLR4/MyD88-mediated NF-κB pathway and the regulation of liver metabolism.